ϒ(nS) polarizations versus particle multiplicity in pp collisions at s=7 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Erö,J; Fabjan,C; Flechl,M; et al. (Physics Letters B, 2016)
The polarizations of the ϒ(1S), ϒ(2S), and ϒ(3S) mesons are measured as a function of the charged particle multiplicity in proton–proton collisions at s=7 TeV. The measurements are performed with a dimuon data sample collected in 2011 by the CMS experiment, corresponding to an integrated luminosity of 4.9 fb−1. The results are extracted from the dimuon decay angular distributions, in two ranges of ϒ(nS) transverse momentum (10–15 and 15–35 GeV), and in the rapidity interval |y|>1.2. The results do not show significant changes from low- to high-multiplicity pp collisions, although large uncertainties preclude definite statements in the ϒ(2S) and ϒ(3S) cases.